Evaluasi Koordinasi Pelayanan Kesehatan Lintas Provinsi pada Masa Tanggap Darurat Bencana Gunung Merapi Tahun 2010 - Sri Purwaningsih; Laksono Trisnantoro; Bella Donna (Center for Health Policy and Management, 2014)
Background: Natural disasters influence human health and prosperity. The increasing tendency for natural disaster has become a priority in the disaster management in Indonesia. Gunung Merapi erupted on October 26, 2010. The eruption continued until November 2010. The disaster led to huge life tolls and injuries. It also caused substantial and extensive dam- ages and losses in four main regions, Sleman Regency in the Province of DI Yogyakarta, Magelang, Klaten, and Boyolali Regencies in the Province of Central Java. The data issued on December 13, 2010 reported 388 life tolls, 2.786 inpatient inju- ries, 62.923 outpatients injuries, and up to 21.338 refugees. To anticipate the spread of negative effects on the victim health due to Gunung Merapi eruption, the Provincial Health Office of DIY and Central Java had cross-provincial coordination, orga- nization, communication, and leadership.Method: A qualitative research was conducted using case study design. Subjects of the study were informants who played important roles in the coordinative process in the Prov- ince of DI Yogyakarta and Central Java. The data were col- lected by means of document investigation, direct observa- tion, and in-depth interviews. Data validity was checked by means of source, method, and data triangulation. Results: To realize an effective and efficient healthcare dur- ing the emergency response period after Gunung Merapi erup- tion, an integrated command organization was established to involve the two provinces – DI Yogyakarta and Central Java. The organization had daily coordination meetings by means of direct communication in terms of meetings and indirect com- munication using teleconference. Information could be received and transmitted quickly by means of sms gateway and email. Leadership applied during the emergency response period was command in nature, rather than authoritarian style. Conclusion: Cross-provincial healthcare coordination during the emergency response period after Gunung Merapi eruption in 2010 worked in a sufficiently effective way, since no ex- traordinary cases occurred at that time. Latar Belakang: Bencana alam selalu mempengaruhi kesehat- an dan kesejahteraan manusia. Bencana alam yang terus meningkat telah menjadi sebuah prioritas penanganan bencana di Indonesia. Pada tanggal 26 Oktober 2010, Gunung Merapi mengalami erupsi dan berlanjut sampai dengan awal Novem- ber 2010. Jumlah korban yang meninggal maupun luka-luka cukup banyak, serta menyebabkan kerusakan dan kerugian yang meluas di empat wilayah yaitu kabupaten Sleman di Provinsi DI Yogyakarta, Kabupaten Magelang, Klaten dan Boyolali di Provinsi Jawa Tengah. Informasi yang diperoleh pada tanggal 13 Desember 2010, data meninggal dunia 388 orang, rawat inap sejumlah 2.786 orang, rawat jalan 62.923 orang dan jumlah pengungsi sampai 21.338 orang. Untuk mengantisipasi meluasnya dampak negatif terhadap kesehatan yang ditimbulkan akibat erupsi Gunung Merapi, Dinas Kesehatan Provinsi DIY dan Jateng melaksanakan koordinasi, pengorgani- sasian, komunikasi dan kepemimpinan. Metode Penelitian: Penelitian kualitatif dengan rancangan studi kasus. Subyek penelitian adalah informan yang memiliki peranan penting dalam proses koodinasi di Provinsi D.I. Yog- yakarta dan Jateng. Pengumpulan data menggunakan studi dokumentasi, observasi langsung, dan wawancara mendalam. Validitas data menggunakan triangulasi sumber, metode, dan data.Hasil Penelitian: Untuk mencapai pelayanan kesehatan yang efektif dan efisien pada masa tanggap darurat bencana Gunung Merapi, dibentuk organisasi komando terpadu yang melibatkan dua Provinsi yaitu DI. Yogyakarta dan Jateng, melaksanakan koordinasi melalui rapat harian menggunakan komunikasi langsung dengan pertemuan dan tidak langsung dengan tele- conference. Penerimaan dan pengiriman informasi cepat melalui sms gateway dan email. Gaya Kepemimpinan yang diterapkan pada masa tanggap darurat bersifat komando dan tidak otoriter. Kesimpulan: Koordinasi pelayanan kesehatan lintas provinsi pada masa tanggap darurat Gunung Merapi tahun 2010 berjalan cukup efektif, karena pada saat itu tidak terjadi kasus KLB.